Konstruksi Berita Tragedi Itaewon Dalam Media Daring Kompas.Com Dan Tempo.Co: Analisis Framing Pan Dan Kosicki - Dellaviane Syarafina; Hendra Setiawan (Peneliti.net, 2023)
The Itaewon tragedy closed the month of October which deeply hit a number of people. Because the community's activities in celebrating the Halloween ended tragically by indirectly sacrificing their own lives. This has become a public concern which has taken up a lot of perceptions from various media. Therefore, the author aims to determine the perception of the media in reporting. The framingofeach news story is of course different, in this study the author made a comparison between Kompas.com and Tempo.co party tragedy halloween Itaewonanalysis model framing Zhongdan Pan and Gerald M. Kosicki'sIn this study, the authors used a qualitative-descriptive method as a basis for explaining the results and discussion with an approach that uses alibrary research. The results show that the writer found twenty-two titles, among others in Kompas.com found fifteen reports, meanwhile, in Tempo.co found seven reports regarding the Itaewon Tragedy for the period of 30 October 2022. The two media have differences and similarities in framing (framing) each news.